Adoption of Islamic banking in Pakistan an empirical investigation - Shahab Aziz; Zahra Afaq (Cogent Business & Management, 2018)
The purpose of this paper is to investigate the factors affecting individuals' intentions to adopt Islamic banking. Most of the previous studies have used theory of reasoned action and theory of planned behaviour; however, decomposed theory of planned behaviour, which is proven robust and superior, has been used in very few studies. The present study gauges this gap and proposes a comprehensive model for adoption of Islamic banking. The study also incorporated antecedents of attitude, subjective norms and perceived behavioural control to enhance understanding of factors relevant to the adoption of Islamic banking. A sample of 186 bank customers has been selected for data collection. Variance-based partial least-squares structural equation modelling was employed for data analysis. Results show that attitude and subjective norms have significant positive relationship with intention to adopt Islamic banking. The result depicts that attitude is determined by awareness, uncertainty, relative advantage and compatibility. Subjective norm is determined by normative beliefs. Perceived behavioural control is determined by self-efficacy and resource facilitation condition. The findings of the study are important for Islamic banks to revamp their marketing strategies. Marketing managers should try to develop positive attitude through creating awareness and benefits of Islamic banking services. Positive word of mouth is also an important aspect which can be created through enhancing the service delivery to the existing customers.
Keywords: 650